Rôle de l’environnement social et de types d’écoles sur les performances en mathématiques des élèves dans les écoles primaires de Goma - BYANJIRA, John Kissa SHAMAVU (IJRDO- Journal of Educational Research, 2023)
This article aims to provide a new look at the question of the effects of types of schools and the social environment on the mathematics performance of students in the final stage of primary education based on empirical research by questionnaire (n=1290) among students from 32 primary schools in Goma. The question raised is that of establishing a general link between the social environment and performance in mathematics on the one hand, and the link between performance in mathematics, the type of schools and the social environment of the learner on the one hand. ’somewhere else. Based on the theory of school mix and on the typology of schools, the data analyzed using SPSS software made it possible to show a significant relationship between performance in mathematics and the type of schools attended by the learners. The results of the regression model indicate that the social environment/neighborhood of residence of the learners does not have significant effects on mathematics performance. Multivariate multilevel research is essential to seek the causal link of the social environment on mathematics achievement.